Growth of the Bacteriocin-Producing Lactobacillus sakei Strain CTC 494 in MRS Broth Is Strongly Reduced Due to Nutrient Exhaustion: a Nutrient Depletion Model for the Growth of Lactic Acid Bacteria - Leroy, Frédéric (American Society for Microbiology, 2001)
Although commercial MRS broth has been designed to allow excellent growth of lactobacilli, most of these bacteria are still subjected to a self-inhibiting process. The most likely explanation is the accumulation of lactic acid or other toxic end products and the depletion of nutrients. In this study, the self-inhibition of Lactobacillus sakei CTC 494 was analyzed in a kinetic way, and a nutrient depletion model was set up to describe the growth inhibition process. This simple model has considerable advantages compared to commonly used descriptive models such as the logistic growth equation. It offers a better fit and a more realistic description of the growth data by taking into account both growth inhibition due to lactic acid production and changes in growth rates due to nutrient depletion. Depending on the fermentation conditions, in MRS broth there appears to be a strong decrease of the specific growth rate over time. Some undefined compounds present in the complex nitrogen source of MRS broth appear to be of crucial importance because of their limited availability. Moreover, nutrient availability affects bacteriocin production through its effect on cell growth as well as on the bacteriocin production per cell. A plateau value for the bacteriocin production by L. sakei CTC 494 was observed.